A novel HD‐Zip I/C2H2‐ZFP/WD‐repeat complex regulates the size of spine base in cucumber. Issue 6 (30th January 2022) - Yang, Sen; Wang, Yueling; Zhu, Huayu; Zhang, Minjuan; Wang, Dengke; Xie, Kuixi; Fan, Pengfei; Dou, Junling; Liu, Dongming; Liu, Bin; Chen, Chunhua; Yan, Yan; et al.
Summary: Fruit spine is an important trait in cucumber, affecting not only commercial quality, but also fruit smoothness, transportation and storage. Spine size is determined by a multi‐cellular base. However, the molecular mechanism underlying the regulation of cucumber spine base remains largely unknown. Here, we report map‐based cloning and characterization of a spine base size 1 ( SBS1 ) gene, encoding a C2H2 zinc‐finger transcription factor. Near‐isogenic lines of cucumber were used to map, identify and quantify cucumber spine base size 1 ( CsSBS1 ). Yeast‐hybrid, bimolecular fluorescence complementation (BiFC), co‐immunoprecipitation (Co‐IP) and RNA‐sequencing assays were used to explore the molecular mechanism of CsSBS1 in regulating spine base size development. CsSBS1 was specifically expressed in cucumber ovaries with particularly high expression in fruit spines. Overexpression of CsSBS1 resulted in large fruit spine base, while RNA‐interference silencing of CsSBS1 inhibited the expansion of fruit spine base. Sequence analysis of natural cucumber accessions revealed that CsSBS1 was lost in small spine base accessions, resulting from a 4895 bp fragment deletion in CsSBS1 locus. CsSBS1 can form a trimeric complex with two positive regulators CsTTG1 and CsGL1 to regulate spine base development through ethylene signaling. A novel regulator network is proposed that the CsGL1/CsSBS1/CsTTG1 complex plays a significant role in regulating spine base formation and size, which offers a strategy for cucumber breeders to develop smooth fruit.